(Thiazol-2-yl)hydrazone derivatives from acetylpyridines as dual inhibitors of MAO and AChE: synthesis, biological evaluation and molecular modeling studies. (2nd November 2015) - D'Ascenzio, Melissa; Chimenti, Paola; Gidaro, Maria Concetta; De Monte, Celeste; De Vita, Daniela; Granese, Arianna; Scipione, Luigi; Di Santo, Roberto; Costa, Giosuè; Alcaro, Stefano; Yáñez, Matilde; Carradori, Simone
Abstract: Several (thiazol-2-yl)hydrazone derivatives from 2-, 3- and 4-acetylpyridine were synthesized and tested against human monoamine oxidase (hMAO) A and B enzymes. Most of them had an inhibitory effect in the low micromolar/high nanomolar range, being derivatives of 4-acetylpyridine selective hMAO-B inhibitors also at low nanomolar concentrations. The structure–activity relationship, as confirmed by molecular modeling studies, proved that the pyridine ring linked to the hydrazonic nitrogen and the substituted aryl moiety at C4 of the thiazole conferred the inhibitory effects on hMAO enzymes. Successively, the strongest hMAO-B inhibitors were tested toward acetylcholinesterase (AChE) and the most interesting compound showed activity in the low micromolar range. Our results suggest that this scaffold could be further investigated for its potential multi-targeted role in the discovery of new drugs against the neurodegenerative diseases.